ANALISA HUKUM PERKAWINAN SATU MARGA MENURUT ADAT BATAK TOBA - Elly AM. Pandiangan (to-ra, 2016)
Marriage is born inward ties between a man and a woman as husband and wife, with the aim of forming family ( households ) happy and lasting based on belief in god. There are also has given understanding marriage is one of events that are extremely important in livelihood our society, for marriage is not only related to women and men will bridegroom just, but also parents both sides, his brethren, even family their families each. Marriage was on the community generally particularly was toba, one marga marriage between men and women banned, and until now the ban still retained. If someone is breaking then given punishment customary, namely in cerai life, or expelled from his home, however the punishment in accordance with the development of the age of those who do the marriage of one marga issued from customary. To avoid that the marriage of one marga not occur, so parents should tell his sons as the next generation that the marriage of one marga forbidden.With any reason not the marriage of one marga not allowed to including the ordinal of a breed of to generation may not be used to give permission to do the marriage of one marga, including by reason in love, moreover the in particular the batak toba bound with dalihan natolu, and also on the day when the so when the first both sides questions and answer each ask marga, for the purpose to know familial relationships. Besides if connect to health that marriage with brother the get two copies genes who have lost compared with marriage who come from outside the family. With what mentioned above, until now ban the marriage of one marga have to be preserved. In addition to those who violations of the ban was right and relevant given punishment. Kata Kunci: Perkawinan Marga Batak Toba